2019
DOI: 10.4236/gep.2019.78006
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Impacts of Climate Change on Maize (<i>Zea mays</i> L.) Growth and Productivity: A Review of Models, Outputs and Limitations

Abstract: The use of crop modelling in various cropping systems and environments to project and upscale agronomic decision-making under the facets of climate change has gained currency in recent years. This paper provides an evaluation of crop models that have been used by researchers to simulate maize growth and productivity. Through a systematic review approach, a comprehensive assessment of 186 published articles was carried out to establish the models and parameterization features, simulated impacts on maize yields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 70 publications
(54 reference statements)
1
12
0
1
Order By: Relevance
“…3 that the key adaptation strategy by the farmers in the western region of Kenya was a change of planting decision by either planting early or delaying planting date. This supports the findings of a review study by Kogo et al (2019c) which established that change of planting dates was one of the major agro-adaption options towards mitigating the impacts of climate change on crop production. According to Lv et al (2020), adjusting of planting date is one of the strategies used by farmers to maintain or increase crop yields under climate change.…”
Section: (I) Early/delayed Plantingsupporting
confidence: 87%
“…3 that the key adaptation strategy by the farmers in the western region of Kenya was a change of planting decision by either planting early or delaying planting date. This supports the findings of a review study by Kogo et al (2019c) which established that change of planting dates was one of the major agro-adaption options towards mitigating the impacts of climate change on crop production. According to Lv et al (2020), adjusting of planting date is one of the strategies used by farmers to maintain or increase crop yields under climate change.…”
Section: (I) Early/delayed Plantingsupporting
confidence: 87%
“…In this study, we use daily climate projections from GCMs which have been previously bias-corrected [15]. The cumulative distribution function transfer (CDFt) method [16,17], using a univariate quantile-quantile method, reducing the bias in daily data.…”
Section: Climate Projections In West Africamentioning
confidence: 99%
“…The cumulative distribution function transfer (CDFt) method [16,17], using a univariate quantile-quantile method, reducing the bias in daily data. By computing various climatic indices such as seasonal rainfall, dry spells and onset of the rains, that is demonstrated that this technique strongly reduces the errors in the present-day simulations of the CMIP5 models compared to observed data [15](WFDEI, [18] over the 1979-2013 period), and reduces the spread between the models for the different RCPs. Climate model outputs have been bi-linearly interpolated onto a 0.5 • linear grid before bias correction.…”
Section: Climate Projections In West Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Climate change has caused inter-seasonal yield variability and negative impact on crop growth, development and production. The major challenges to agriculture are related to climate change severity and occurrence of extreme weather events, such as floods, drought and heat haves but also to agricultural management (application of fertilizers, tillage, agrochemicals) [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%